Do maximal aerobic power and blood lactate concentration affect Specific Judo Fitness Test performance in female judo athletes? - Garbouj, H; Selmi, MA; Haj Sassi, R; Haj Yahmed, M; Chamari, K; Chaouachi, A (Biology of Sport, 2016)
The Special Judo Fitness Test (SJFT) has become the test most widely used by coaches and physical trainers for assessment of competitors’ judo-specific physical aptitude and training programme prescription. The aim of this study was to investigate the relationship between the SJFT performance indices and both maximal aerobic power and the level of blood lactate concentrations in female judo athletes. Seventeen female judokas (age: 21.9±1.6 years, body mass: 74.6±27.4 kg, height: 164.5±8.6 cm; BMI: 27.1±8.0 kg • m-2) took part in this study. All participants performed the SJFT, 20 m multi-stage shuttle run test (MSRT), and 30 m straight sprint test (SST), from which we calculated both acceleration (10 m) and the maximal anaerobic speed (MAnS: flying 20 m sprint). A blood sample was taken 3 min after the SJFT. The number of throws was significantly correlated with estimated VO2max (r=0.795, p=0.0001) and both acceleration (r=0.63, p =0.006) and MAnS (r=0.76, p=0.0004). Peak blood lactate recorded after the SJFT was 13.90±1.39 mmol • l-1. No significant correlation was found between blood lactate concentration and the SJFT performance indices. The lack of significant correlation between blood lactate and SJFT performance suggests that lactic anaerobic metabolism has no effect on this type of judo-specific supra-maximal exercise. The observed results can provide coaches and strength and conditioning professionals with relevant information for the interpretation of SJFT performance and the prescription of specific training programmes for female judo athletes.